Analisis Faktor-Faktor Penentu Kinerja Keuangan Perbankan Konvensional: Peran Good Corporate Governance, Profitabilitas, Likuiditas, dan Struktur Modal - Dwi Anggin Pratiwi; Titin Eka Ardiana; Rizki Listyono Putro (Forum Kerjasama Pendidikan Tinggi, 2026)
This study aims to analyze the influence of good corporate governance, profitability ratios, liquidity ratios, and capital structure on the financial performance of conventional banking companies listed on the Indonesia Stock Exchange for the 2020–2024 period. This research is motivated by high interest rates, increasing cost of funds, and competition in the banking industry that affect the stability and financial performance of conventional banks. The study population includes all conventional commercial banks in Indonesia, with a sample of 29 banking companies selected using a purposive sampling technique with a total of 145 observation data. Data analysis was performed using panel data regression with the help of EViews 12 through model selection tests, multicollinearity tests, heteroscedasticity tests, partial tests (t), and simultaneous tests (F). The results of the study indicate that the profitability ratio has a positive and significant effect on financial performance with a p-value of 0.0000. While good corporate governance (p-value = 0.8625), liquidity ratio (p-value = 0.9995), and capital structure (p-value = 0.1541) do not have a significant effect partially. Simultaneously, all independent variables have a significant effect on financial performance (Prob. F = 0.0000) with an Adjusted R² value of 0.8886, indicating that 88.86% of the variation in financial performance can be explained by the research model.